Konsep Worldview: Usaha Melengkapi Konsep Struktur dalam Teori Strukturasi Giddens - Johanis Putratama Kamuri (Jurnal Filsafat "WISDOM", 2021)
The aim of this paper is to complete the concept of structure, in structuration theory, with the concept of worldview. Giddens' structuration theory emphasizes structure as a result as well as a medium for the regularization of social practice. It emphasizes structure in cognition but ignores the structure of society. As a result, the theory does not explain how social practices that produce virtual structures can exist and be practiced continuously in society, before virtual structures are formed in agents’ cognition? Therefore, the concept of structure needs to be complemented with the concept of worldview, which emphasizes the existence of a social structure that reveals itself through cultural components. Systematic reviews, on MacIntyre's thoughts and various thoughts related to the worldview, show that cultural components produce the regularization of social practice. The result is the formation of the worlview as the medium for social practice. It means that the worldview concept emphasizes the correspondence of the society's objective structure and the cognitive structures. This concept can show the existence of the structure of society and the influence of cultural components in it on the regularization of social practice and the formation of the worldview. Worldview concept answers the research problem.